ANALISIS SOSIAL DAN EKONOMI NELAYAN GILLNET DI DESA BOGAK KECAMATAN TANJUNG TIRAM KABUPATEN BATU BARA PROVINSI SUMATERA UTARA - Wulan Iman Sari; Budi Utomo; Amanatul Fadhilah (AQUACOASTMARINE, 2018)
One of the methods to find out the socio-economic condition of gillnet fishermen in Bogak Village, Tanjung Tiram subdistrict, Batu Bara Regency is to study the socio-economic condition of fishermen community. The purpose of this research is to know social analysis of gillnet fishermen in Bogak Village, Tanjung Tiram Subdistrict. To know the economic analysis of gillnet fishermen in Bogak Village, Tanjung Tiram Subdistrict, Batu Bara regency. Data analysis know the socio-economic condition of gillnet fisherman community in Bogak Village, this research was conducted through interview with the community and questionnaire distribution. Social analysis of fishermen organization of environmental income education, Primary Data of Secondary Data, fisherman respondent, Likert scale, and economic analysis. The results showed the socio-economic condition of the community in Bogak Village, Tanjung Tiram District, Batu Bara regency, where the fishermen's income per month is Rp 1,500,000. relationship of the influence of social and economic conditions on fishermen society is the limited education and the state of a poor community home. So that greatly affect the environmental education as well as the behavior of the fishermen community life.Keywords: Social and Economic Analysis of Fishermen, Gillnet, Fisherman society, Traditional.